PENERAPAN KURIKULUM MERDEKA DI SMA NEGERI 14 MEDAN DALAM MENGIMPLEMENTASIKAN PENDIDIKAN YANG SESUAI DENGAN KODRAT ALAM DAN KODRAT ZAMAN - Tuasibarani, Ramot Tua; Susilawati, Evi; Gultom, Rumesti (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
Kurrikurlurm Merderka is a harmonious Kurrikurlurm in terms of providing education that is in harmony with the nature of nature and the times. With the implementation of the Merrderka curriculum at Ngerri 14 Merdan High School, students can maximize their potential. The variety of learning in their curriculum does not only depend on one thing. Learning can be carried out outside of class, this can stimulate students to be more creative, innovative and critical. Apart from that, their curriculum also teaches teachers to be able to think openly and see things from various perspectives, especially in observing students' characteristics. Because with the existence of a free curriculum, there is no longer any discrimination among students, all students receive treatment that is equal to themselves so that the potential of students can be maximized. Education that is in line with the nature of nature and the times will be successful if students and teachers both implement their curriculum in accordance with what is interpreted by the government in its implementation. Apart from that, the key features of the surksers to develop their curriculum are various implementations of education that are in line with the nature of nature and the times, there is a teacher's mindset that must be open and accept changes and also adapt itself to be more creative and innovative in developing education. meaningful to students